ANALYZING TEACHERS' ABILITY IN IMPLEMENTING ONLINE LEARNING AT SDN 005 KEMPAS JAYA - Sugiarto Sugiarto (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
The teachers’ ability in online learning needed to be analyzed in order to make them able to provide a clear picture of the weaknesses that would arise in learning. This research was a school action research that utilized quantitative research method. This research assessed the teachers’ ability by generating numbers as an illustration of the number of 10 teachers at SDN 005 Kempas Jaya. The results of the research obtained that the average score for indicator 1 about the preparation of lesson plans was 74.5. Then, the teachers’ ability in determining basic competencies and making learning objectives were categorized as good and the average score of indicator 2 was 81.5 and indicator 3 was 84.5, while the score for indicator 4 was 76, the score for indicator 5 was 78, and the score for indicator 6 was 73.5. This assessment was seen from the pre-learning process, while during the implementation of learning, the least was indicator 1 which was the teacher's ability to make online learning applications for 67, and indicator 5 which was the teacher's ability to direct students to work on student worksheets for 62. Ths was because it was difficult to control students due to limited space and time. For this reason, teachers should be given trainings in implementing online learning.